AUTOMATION OF ELECTRONIC DOCUMENT CIRCULATION - G'aniyev Xurshidbek Yoqubjon o'g'li; Sayidova Mekhrinoz O‘ktamjon qizi (Web of Journals Publishing, 2025)
This article analyzes the nature of electronic document circulation, its advantages and implementation based on modern technologies. Consideration will be given to how electronic document circulation will create convenience for enterprises, state organizations and individuals. Also, the main stages of the introduction of electronic document circulation and the ways of its effective organization are considered.
Keywords: Electronic document circulation, digital documents, electronic archive of documents, automation, information technologies, document management.